2014
DOI: 10.1016/j.jcbs.2014.08.005
|View full text |Cite
|
Sign up to set email alerts
|

The moderating role of experiential avoidance in the relationship between posttraumatic stress disorder symptom severity and cannabis dependence

Abstract: The relationship between cannabis use and posttraumatic stress disorder (PTSD) has received increased scientific scrutiny in recent years. Consistent with this research, studies provide evidence that many individuals with PTSD use cannabis to reduce negative affect and other unpleasant internal experiences associated with PTSD. However, no research to date has explored factors that may be associated with an increased likelihood of cannabis misuse among individuals with PTSD. Consequently, this study explored t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…In a study of statistics anxiety, willingness to experience anxiety buffered the effect anxiety had on statistics exam performance (Sandoz, Butcher, & Protti, 2017). Further, in two studies of PTSD, avoidance exacerbated PTSD's link with impulsive behaviors (Bordieri, Tull, McDermott, & Gratz, 2014;Gratz & Tull, 2012). Findings from these studies support the moderating role of non-acceptance: Accepting distress facilitates goal attainment and non-acceptance inhibits it.…”
Section: Cognitive Fusion and Goal Dysregulationmentioning
confidence: 88%
“…In a study of statistics anxiety, willingness to experience anxiety buffered the effect anxiety had on statistics exam performance (Sandoz, Butcher, & Protti, 2017). Further, in two studies of PTSD, avoidance exacerbated PTSD's link with impulsive behaviors (Bordieri, Tull, McDermott, & Gratz, 2014;Gratz & Tull, 2012). Findings from these studies support the moderating role of non-acceptance: Accepting distress facilitates goal attainment and non-acceptance inhibits it.…”
Section: Cognitive Fusion and Goal Dysregulationmentioning
confidence: 88%
“…Research by Bonn-Miller and colleagues has shown that PTSD symptom severity is positively related to the use of marijuana to cope with negative internal experiences (Bonn-Miller et al, 2007; 2011), and a recent study by Bordieri et al (2014) revealed a positive association between PTSD symptom severity and marijuana dependence only among individuals with average to high levels of experiential avoidance (i.e., the tendency to avoid unwanted internal experiences; Hayes et al, 1996). If our findings are due to heightened emotional avoidance among marijuana dependent patients with PTSD, such disruptions in the emotional processing of fear-relevant information may ultimately inhibit extinction of the fear and anxiety response among these individuals, contributing to the maintenance of PTSD (Foa and Kozak, 1986; Rauch and Foa, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence linking avoidance, PTSD, and marijuana use. Experiential avoidance (the tendency to avoid aversive internal experiences) moderates the relationship between PTSD severity and marijuana dependence (Bordieri, Tull, McDermott, & Gratz, ), while emotional distress tolerance (Potter et al., ) and nonjudgmental acceptance (similar to mindfulness, essentially the opposite of avoidance; Bonn‐Miller, Vujanovic, & Twohig, ) mediate the relationship between PTSD symptoms and marijuana use. If marijuana use does serve an avoidance function, symptom improvement will, theoretically, be temporary at best and will stymie emotional processing putatively necessary for recovery.…”
Section: Potential Harmful Psychiatric Effects Of Regular Marijuana Usementioning
confidence: 99%